Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.30843/nzpp.2012.65.5396
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of <i>Venturia inaequalis</i> to myclobutanil penconazole and dodine in relation to fungicide use in Hawkes Bay apple orchards

Abstract: A survey of Integrated Fruit Production and organic apple orchards in Hawkes Bay in 201011 investigated sensitivity of Venturia inaequalis isolates to demethylation inhibitor (DMI) and dodine fungicides EC50 values from mycelial growth assays for two DMIs showed continued loss of sensitivity since the 1990s Sensitivity was lower in orchards where DMI usage exceeded resistance management guidelines The most DMIsensitive isolates were found in one organic orchard Plant inoculations showed that black spot control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Fungicides with site-speciic modes of action that are used in apple spray programmes for control of black spot (scab), caused by Venturia inaequalis, include demethylation inhibitor (DMI), dodine, quinone outside inhibitor (QoI) and anilopyrimidine (AP) groups. These fungicides are currently being investigated in relation to fungicide resistance development in V. inaequalis (Beresford et al 2012;Viljanen-Rollinson et al 2013;Larsen et al 2013;FRAC 2013). The potential impacts of resistance on the New Zealand apple industry include increased economic losses from increased incidence of black spot in orchards and threats to market access from diseased fruit and increased fungicide residues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungicides with site-speciic modes of action that are used in apple spray programmes for control of black spot (scab), caused by Venturia inaequalis, include demethylation inhibitor (DMI), dodine, quinone outside inhibitor (QoI) and anilopyrimidine (AP) groups. These fungicides are currently being investigated in relation to fungicide resistance development in V. inaequalis (Beresford et al 2012;Viljanen-Rollinson et al 2013;Larsen et al 2013;FRAC 2013). The potential impacts of resistance on the New Zealand apple industry include increased economic losses from increased incidence of black spot in orchards and threats to market access from diseased fruit and increased fungicide residues.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of Hawke's Bay apple orchards in the 2010-11 season (Beresford et al 2012) indicated that DMI sensitivity in V. inaequalis had decreased since surveys in the 1990s (Whelan et al 1992;Bakker et al 1995), to a degree where loss of black spot control could now be expected in some orchards. There was no evidence of a loss of sensitivity to dodine in Hawke's Bay since the 1990s (Bakker et al 1995;Bakker 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen V. inaequalis isolates from a Hawke's Bay survey during 2010-2011 (Beresford et al 2012) were selected from either organic orchards with no synthetic fungicide use for at least 5 years or from Integrated Fruit Production (IFP) orchards with a history of high QoI use (Table 1). The QoI-sensitivity of 12 of these isolates was determined by comparing mycelial colony diameter on agar amended with triloxystrobin (Twist® SC containing 500 g triloxystrobin/litre) with that on non-amended agar.…”
Section: Mycelial Growth Assay For Sensitivity To Trifloxystrobinmentioning
confidence: 99%
“…It was subsequently used in a nationwide survey to determine how widespread QoI resistance was in New Zealand apple orchards. The method was developed using V. inaequalis isolates selected from a 2010-11 survey of Hawke's Bay apple orchards for dodine and demethylation inhibitor fungicide sensitivity (Beresford et al 2012) and was then used to test isolates collected in a nationwide survey from orchards in Hawke's Bay, Nelson, Waikato and Otago in 2011-12.…”
Section: Introductionmentioning
confidence: 99%
“…This could threaten New Zealand apple exports by reducing growers' ability to meet market standards for disease-free and chemical residue-free fruit. Recent evidence of ield resistance in New Zealand has led to investigation of the fungicide groups demethylation inhibitor (DMI) and dodine (Beresford et al 2012;Beresford et al 2013), quinone outside inhibitor (QoI) (Viljanen-Rollinson et al 2013) and anilinopyrimidine (AP) fungicides, which are the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%